Desain Camouflage Tower di Kawasan Kota Baru Parahyangan Padalarang-Bandung - Hasanah Putri; Radial Anwar; Dea Farah Amalia (Jurnal Rekayasa Elektrika, 2021)
Kota Baru Parahyangan residential area, located in Padalarang sub-district of Bandung, has the quality and coverage of 3G and 4G cellular services that are not optimal, thus it has become a complaint of customers to the cellular providers. Therefore in this article a camouflage tower or Outdoor Distributed Antenna System (ODAS) is designed, which is a unique concept that helps in prividing connectivity in location where conventional tower construction is not permitted due to various regulations. This camouflage tower design aims to increase the number of cellular antennas but with minimal costs, land and human resources. In addition, this camouflage tower design has a high aesthetic value to be implemented in these elite residential areas. From the design and implementation results for 4G, the Reference Signal Received Power (RSRP) value is 70% at a value -90 dBm and Signal-to-Interference Noise Ratio (SINR) 70% at a value 5 dB according to the Key Performance Indicator (KPI) provider standard, while for 3G the Received Signal Code Power (RSCP) value is 70% at a value -78 dBm and Ec / No -12 dB. This shows that the quality and coverage both of 3G and 4G cellular services in this region have reached the target cellular providers.